SPLENIC ARTERY EMBOLIZATION IN PATIENTS UNDERGOING ORTHOTOPIC LIVER TRANSPLANTATION - D. A. Granov; P. G. Tarazov; A. A. Polikarpov; V. V. Borovik; I. O. Rutkin; I. I. Tileubergenov (Вестник трансплантологии и искусственных органов, 2016)
Aim: to analyze the results of embolization of the splenic artery in fi ve patients after orthotopic liver transplantation.Materials and methods. Embolization of the splenic artery was performed 6 times in fi ve (3.2%) of 158 patients who underwent orthotopic liver transplantation in terms from 2 months up to 10 years after surgery. The indications for embolization in 3 cases were the manifestations of hypersplenism syndrome, in 3 others – splenic artery steal syndrome.Results. In 3 cases of splenic artery embolization, performed in connection with the manifestations of hypersplenism: 2 – recurrent disease, 1 – splenic infarction. In all these cases a splenectomy was required. In 3 cases when embolization was performed in connection with the display of the splenic artery steal syndrome remission was achieved, splenectomy was not required.Conclusion. Splenic artery embolization can be considered as a method of treating patients with manifestations of steal syndrome and hypersplenism after orthotopic liver transplantation. The most pronounced effect was achieved in patients with a predominance of manifestations of steal syndrome.